Mild phenotype of CHAT-associated congenital myasthenic syndrome: case series - Murtazina, Aysylu; Borovikov, Artem; Marakhonov, Andrey; Sharkov, Artem; Sharkova, Inna; Mirzoyan, Alena; Kulikova, Sviatlana; Ganieva, Ralina; Zabnenkova, Viktoriia; Ryzhkova, Oksana; Nikitin, Sergey; Dadali, Elena; et al. (Frontiers in Pediatrics, 2024)
Congenital myasthenic syndrome with episodic apnea is associated with pathogenic variants in the CHAT gene. While respiratory disorders and oculomotor findings are commonly reported in affected individuals, a subset of patients only present with muscle weakness and/or ptosis but not apneic crises. In this case series, we describe five individuals with exercise intolerance caused by single nucleotide variants in the CHAT gene. The age of onset ranged from 1 to 2.5 years, and all patients exhibited a fluctuating course of congenital myasthenic syndrome without disease progression over several years. Notably, these patients maintained a normal neurological status, except for the presence of abnormal fatigability in their leg muscles following prolonged physical activity. We conducted a modified protocol of repetitive nerve stimulation on the peroneal nerve, revealing an increased decrement in amplitude and area of compound muscle action potentials of the tibialis anterior muscle after 15–20 min of exercise. Treatment with 3,4-diaminopyridine showed clear improvement in two children, while one patient experienced severe adverse effects and is currently receiving a combination of Salbutamol Syrup and pyridostigmine with slight positive effects. Based on our findings and previous cases of early childhood onset with muscle fatigability as the sole manifestation, we propose the existence of a mild phenotype characterized by the absence of apneic episodes.